Bone Marrow - Mesenchymal Stem Cell and Platelet Rich Fibrin: A Promising Step of Growth Plate Injury Treatment in Rabbit - Yudyanda, Dimas Rangga; Irianto, Komang Agung; Purwati, Purwati (Scripta Medica, 2025)
Background/Aim: Paediatric physeal injuries account for about 30 % of all bone injuries, often affecting growth plates. Current treatments emphasise prevention, as regenerating the damaged physis is challenging. This study aimed to analyse whether combining bone marrow mesenchymal stem-cell (BM-MSC) and platelet-rich fibrin (PRF) can regenerate physis bone.Methods: The twenty-four New Zealand white rabbits, aged 6 weeks, were acclimatised for 1 week. BM-MSC and PRF were then prepared. A physis injury was induced in the proximal tibia of the rabbits, then divided into four groups: control, BM-MSC treatment, PRF treatment, combination of BM-MSC and PRF treatment. After 4 weeks, rabbits were sacrificed and evaluated. The bony bar diameter was measured using haematoxylin-eosin (H&E) staining, while the expression of tumour necrosis factor-alpha (TNF-α), vascular endothelial growth factor (VEGF) and SRY-box transcription factor 9 (SOX-9) was evaluated using immunohistochemistry (IHC). Results: Histology showed that the BM-MSC and PRF combination led to better regeneration than the control, BM-MSC alone, or PRF alone in terms of osteochondral union. SOX-9 indicators showed significant differences between the control vs BM-MSC groups (p = 0.099); BM-SC vs PRF groups (p = 0.032). TNF-α indicators showed no significant differences at all. VEGF indicators showed significant differences between the control vs BM-MSC and PRF groups (p = 0.008); PRF vs BM-MSC and PRF groups (p = 0.021).Conclusion: Administration of BM-MSC, PRF or a combination of BM-MSC and PRF showed comparable effectiveness in osteochondral union based on histological outcomes. Conversely, PRF alone exhibited the highest effectiveness in IHC analysis. However, none of these results were statistically significant.